Investigation on physicochemical and nutritional properties of caulerpa racemosa, gracilaria manilaensis and padina tetrastromatica - Bola, Aroyehun Abdulqudus (2020)
Seaweeds are recognised as an important ingredient of functional foods recommended for daily food due to their unique compositions and nutritional value. This study was the first time conducted whereby three tropical edible seaweeds (Caulerpa species, Gracilaria species, and Padina species) were selected from Western Peninsular Malaysia to investigate their proximate, physicochemical and nutritional properties according to change in season and geographical habitat. Remarkable geographical variability was recorded in the proximate composition of C. racemosa harvested from the pond and wild. Analysis revealed the farm-C. racemosa contain higher concentration of lipids (4.20 ± 0.32 % DW), protein (20.27 ± 0.14 % DW), dietary fiber (27.57 ± 0.14 % DW) and energy values (25.45 ± 0.07 kcal kg−1) than the wild-C. racemosa with higher ash level (44.98 ± 1.60 % DW). G. manilaensis harvested in November during the Northeast monsoon (NEM) showed a relatively higher level of proteins (19.39 ± 0.12 % DW), carbohydrates (39.58 ± 0.20 % DW), dietary fibers (31.07 ± 1.08 % DW) and energy value (27.22 ± 0.11 kcal kg−1) than the G. manilaensis collected in August during Southwest monsoon (SWM) with a significant higher ash content (38.48 ± 0.23 % DW). Amongst the seaweeds P. tetrastromatica revealed ash levels of (64.819 ± 0.26 % DW) comparatively higher than both C. racemosa and G. manilaensis. Investigation of the fatty acids (FAs) profiles showed palmitic acid (C16:0) was the most abundant ranging from (83.87 – 89.29 %) in G. manilaensis, followed by (51.70 – 63.27 %) C. racemosa and (0.83 %) P. tetrastromatica. Furthermore, oleic acid (C18:1) constituted the dominant monounsaturated fatty acids (MUFA) occurring at (5.80 – 6.33 %) in C. racemosa, followed by (1.47- 6.33 %) G. manilaensis and (0.40 %) in P. tetrastromatica. Total amino acid content occurred between (64.63 – 159.69 mg/g) in C. racemosa, (122.43 – 163.58 mg/g) in G. manilaensis and (61.02 mg/g) in P. tetrastromatica. With respect to physical properties, water holding capacity (WHC) and oil-holding capacity (OHC) showed significant difference according to habitat and seasonal fluctuations. Total phenol content were (96.91 - 178.78 ± 5.93 mg GAE/g), (74.05 – 220. 36 mg GAE/g) and (61.20 mg GAE/g) for C. racemosa, G. manilaensis and P. tetrastromatica respectively. GC-MS analysis revealed the presence of phytochemical compounds including ether, aldehyde, ester, fatty acids, terpenes, sterols, and organic acids responsible for their antioxidant activities. Overall, this thesis revealed that physicochemical and nutritional value of seaweeds have geographical and seasonal variations and that its regular consumption may add benefits to human.